2006
DOI: 10.1111/j.1574-6968.2006.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular characterization of a lipase produced by Rhizopus oryzae

Abstract: A novel strain of Rhizopus oryzae WPG secretes a noninduced lipase (ROLw) in the culture medium; purified ROLw is a protein of 29 kDa, the 45 N-terminal amino acid residues were sequenced, this sequence is very homologous to Rhizopus delemar lipase (RDL), Rhizopus niveus lipase (RNL) and R. oryzae lipase (ROL29) sequences; the cloning and sequencing of the part of the gene encoding the mature ROLw, shows two nucleotides differences with RDL, RNL and ROL29 sequences corresponding to the change of the residues 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 27 publications
4
25
0
Order By: Relevance
“…Rhizopus oryzae was cultivated as described previously (Ben Salah et al 2006). E. coli was cultivated in LuriaBertani medium.…”
Section: Bacterial Strains Plasmids and Mediamentioning
confidence: 99%
See 4 more Smart Citations
“…Rhizopus oryzae was cultivated as described previously (Ben Salah et al 2006). E. coli was cultivated in LuriaBertani medium.…”
Section: Bacterial Strains Plasmids and Mediamentioning
confidence: 99%
“…In previous work Ben Salah et al (2006), have produced, purified to homogeneity from the culture medium, a lipase from a novel strain of Rhizopus oryzae WPG (ROLw) and showed that the amino acid primary sequence of the 29 kDa mature ROLw lipase was 99.3% identical to Rhizopus oryzae lipase ROL32 (Sayari et al 2005), RDL (Derewenda et al 1994) and 98.9% identical to 269 amino acids in Rhizopus niveus lipase (RNL; Kohno et al 1994).…”
mentioning
confidence: 98%
See 3 more Smart Citations